Dietary citrus flavonoid extract improves lactational performance through modulating rumen microbiome and metabolites in dairy cows. Issue 1 (9th December 2022) - Yu, Shiqiang; Li, Liuxue; Zhao, Huiying; Zhang, Shuyue; Tu, Yan; Liu, Ming; Zhao, Yuchao; Jiang, Linshu
Abstract : Supplementing citrus flavonoid extract to the diet of dairy cows significantly improved rumen fermentation and lactational performance via regulating the rumen microbiota and metabolite profiles. Abstract : The effects of dietary supplementation with citrus flavonoid extract (CFE) on milk performance, rumen fermentation, rumen microbiome, rumen metabolome, and serum antioxidant indexes were evaluated. Eight multiparous lactating cows were allocated to a replicated 4 × 4 Latin square with 25-d periods consisting of 20 d of adaptation and 5 d of sampling. Experimental treatments included a control diet (CON) and CON supplemented with 50 g d −1 (CFE50), 100 g d −1 (CFE100), and 150 g d −1 (CFE150). Feeding CFE to dairy cows increased milk production and milk lactose. Milk somatic cell count linearly reduced with increasing CFE amount. Supplementing CFE linearly increased the ruminal concentrations of total volatile fatty acids, acetate, propionate, butyrate, and microbial crude protein. Ruminal lipopolysaccharide linearly decreased with increasing CFE amount. Compared with CON, CFE150 cows exhibited a greater abundance of Firmicutes and a low abundance of Bacteroidetes. Cellulolytic bacteria (genera Ruminococcus, Clostridium, and Butyrivibrio ) and carbohydrate metabolism were enriched in the CFE150 cows. For archaea and viruses, major methanogens (genera Methanobacterium and Methanosarcina ) and phylum Uroviricota were inhibited in the CFE150 cows. Compared with CON, the ruminal concentrations of tyrosine, proline, pyruvate, glucose, and glucose-6-phosphate were higher in the CFE150 cows. The metabolites of citrus flavonoids, such as hippuric acid, hesperetin, and naringenin, were increased in the CFE150 cows. Supplementing CFE significantly improved the antioxidant capacity of the dairy cows. This study highlighted that dietary supplementation with CFE led to significant changes in the rumen microbial composition and metabolites, and consequently resulted in an improved lactational performance of dairy cows.